3D extrusion printing of density gradients by variation of sinusoidal printing paths for tissue engineering and beyond. (1st March 2023) - Kilian, David; Holtzhausen, Stefan; Groh, Wolfram; Sembdner, Philipp; Czichy, Charis; Lode, Anja; Stelzer, Ralph; Gelinsky, Michael
Abstract: During extrusion printing of pasty biomaterials, internal geometries are mainly adjusted by positioning of straightly deposited strands which does not allow realization of spatially adaptable density gradients in x -, y - and z -direction for anisotropic scaffolds or anatomically shaped constructs. Herein, an alternative concept for printing patterns based on sinusoidal curves was evaluated using a clinically approved calcium phosphate cement (CPC). Infill density in scaffolds was adjusted by varying wavelength and amplitude of a sinus curve. Both wavelength and amplitude factors were defined by multitudes of the applied nozzle diameter. For CPC as a biomaterial ink in bone application, porosity, mechanical stiffness and biological response by seeded immortalized human mesenchymal stem cells – adhesion and pore bridging behavior – were investigated. The internal structure of a xyz -gradient scaffold was proven via X-ray based micro computed tomography (µCT). Silicone was used as a model material to investigate the impact of printing velocity and strand distance on the shape fidelity of the sinus pattern for soft matter printing. The impact of different sinus patterns on mechanical properties was assessed. Density and mechanical properties of CPC scaffolds were successfully adjusted without an adverse effect on adhesion and cell number development. In a proof-of-concept experiment, a sinus-adjusted density gradient in an anatomically shaped construct (human vertebral body) defined via clinical computed tomography (CT) data was demonstrated. This fills a technological gap for extrusion-based printing of freely adjustable, continuously guidable infill density gradients in all spatial directions. Statement of significance: 3D extrusion printing of biomaterials allows the generation of anatomically shaped, patient-specific implants or tissue engineering scaffolds. The density of such a structure is typically adjusted by the strand-to-strand distance of parallel, straight-meandered strands in each deposited layer. By printing in a sinusoidal pattern, design of density gradients is possible with a free, spatial resolution in x-, y- and z-direction. We demonstrated that porosity and mechanical properties can be freely adapted in this way without an adverse effect on cell adhesion. With the example of a CT dataset of a human spine, the anisotropic pattern of a vertebral body was resembled by this printing technique that can be translated to various patterns, materials and application. Graphical abstract: Image, graphical abstract